THE ANALYSIS OF SARCASM UTTERANCES FOUND IN BARBIE 2023 MOVIE - Septyanasari, Edylla Isnaini; Hartati, Elysa (Peneliti.net, 2024)
This study explores the types and functions of sarcasm in the Barbie movie released in 2023. Sarcasm, recognized as a powerful tool for conveying hidden messages and social criticism in the movies, serves as a means of evasion and indirect communication. Drawing on Systemic Functional Linguistics, the research focuses on classifying, interpreting, and understanding the functions of sarcasm uttered by various characters in the Barbie movie. The objectives is to find the types and the functions of sarcasm in the movie. Using Camp's theory for classification, the study analyzes 34 instances of sarcasm in the Barbie movie, categorizing them into four types: propositional, lexical, like-prefixed, and illocutionary sarcasm. The results reveal illocutionary sarcasm as the most prevalent type (44.11%), followed by like-prefixed sarcasm (32.35%). The research also identifies ten functions of sarcasm, with delivery of orders being the most common (41.17%). The methodology employed is qualitative, utilizing Spradley's ethnographic analysis model to interpret data obtained from the Barbie movie. The study emphasizes the importance of understanding the cultural and societal influences on sarcasm, considering its impact on interpersonal relationships. In conclusion, this research contributes to a deeper comprehension of sarcasm in the context of movies, particularly in a widely acclaimed movie like Barbie. The study encourages future exploration of the correlation between sarcasm and cultural themes, emphasizing the need for language learners to navigate the complexities of sarcasm and its potential impact on interpersonal dynamics.